Resource utilization method of waste graphite, catalyst and application of catalyst
By crushing, pyrolysis and activation of the graphite electrodes of waste batteries, catalysts are prepared, which solves the problems of low efficiency and high cost of waste graphite resource utilization, and achieves efficient capture and degradation of new pollutants, which is in line with green chemistry and circulation Economic concept.
Patent Information
- Application Number
- CN202410681501.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-05-29
AI Technical Summary
In the prior art, waste graphite has low resource utilization efficiency and high cost of processing and utilization of carbon materials, resulting in resource waste and environmental pollution problems.
By crushing, pyrolyzing and activating the graphite electrodes of waste batteries, a catalyst with a high specific surface area is prepared to capture new pollutants such as antibiotics and analyze the adsorption and degradation of self-doped metals on tetracycline hydrochloride. unique gain effect.
It realizes the simple and easy resource utilization of waste graphite, reduces costs, and improves the capture and degradation efficiency of new pollutants, which is in line with the concept of green chemistry and circular economy.
Smart Images

Figure CN119158587A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for recycling waste graphite, a catalyst and uses thereof, and in particular to a method for recycling anode graphite in waste batteries, a catalyst and uses thereof, and belongs to the field of recycling waste batteries. Background Art
[0002] The vigorous development of new energy electric vehicles has led to a rapid increase in the production and sales of lithium-ion batteries. Graphite is the main anode material in commercial lithium batteries, accounting for 10-20wt.% of the mass of lithium batteries. According to the global anode material shipments and the proportion of graphite anodes, it is estimated that 4 million tons of waste graphite will be generated from waste lithium batteries at the end of their life in the next five years. Waste graphite usually contains a variety of trace or trace metal impurities and toxic and harmful electrolytes, which are difficult to recycle. It is usually burned at high temperatures or discarded in landfills, which results in huge waste of resources and environmental disposal costs. However, existing research mainly focuses on the recovery of valuable metals in the positive electrode of waste lithium batteries, but pays less attention to the large amount of waste graphite produced.
[0003] The resource utilization of waste graphite usually includes: crushing, screening, pickling to remove metal impurities and high temperature to remove organic impurities, and then downgrading it as recycled graphite, or preparing it into energy storage materials such as supercapacitors, or using the highly polluting Hummers method to prepare it into graphene materials. In addition, carbon-based materials, such as carbon nanotubes, graphene, biochar, etc., have received widespread attention in wastewater adsorption treatment in the past decade due to their porous structure and the advantages of being a stable carrier. Waste graphite is a type of carbon-based material and has the potential to be prepared as a carrier for wastewater treatment.
[0004] Reference 1 discloses a graphite-containing electrode regenerated from waste lithium-ion batteries by organic acid pyrolysis and gas phase reduction, and a regeneration method thereof, which provides a technical solution in which waste lithium batteries are discharged, disassembled, and separated to obtain waste graphite powder; the graphite powder is impurity-removed by acid leaching with an organic acid, the graphite after acid leaching is separated into solid and liquid, dried, and then calcined at a high temperature to obtain regenerated graphite.
[0005] Reference 2 discloses a method for preparing supercapacitor electrode materials using waste lithium battery graphite, which provides a technical solution for preparing graphene / MnO2 supercapacitor electrode materials by soaking and cleaning the waste graphite in clean water, roasting and ball milling it for purification, and then adding potassium permanganate to a Teflon inner reactor for hydrothermal reaction.
[0006] Reference 3 discloses a method for preparing graphene oxide by an improved Hummers method, which provides a method for mixing graphite, sodium nitrate and potassium permanganate under ice bath conditions, then placing the mixture in concentrated sulfuric acid, stirring until a slurry-like substance appears, adding deionized water to a beaker while stirring, transferring the beaker to a 90°C constant temperature water bath and continuing to stir, then adding hydrogen peroxide and continuing to stir to obtain a solution, filtering the solution through dialysis to remove excess sulfate ions in the solution, storing it after multiple centrifugation treatments, and finally performing ultrasonic treatment through a constant temperature ultrasonic device to screen out a single layer of graphene oxide.
[0007] However, the methods of regenerating waste graphite into electrode materials or preparing it into graphene have high requirements for equipment and costs, and produce secondary waste streams. None of the above resource recovery methods have industrial application cases. At the same time, the manufacturing process of carbon material adsorbents is usually complicated and expensive, and inevitably requires further carbonization or metal loading to improve the performance of pollutant degradation, which to a certain extent reduces the practicality of these carbon materials. It can be seen that the current circular economy field has an industry contradiction of low efficiency of waste graphite resource recovery and excessively high cost of processing and utilization of new carbon materials.
[0008] Therefore, studying a method for resource utilization of waste graphite and realizing the recycling of waste graphite and coordinated control of new pollutants has become a technical problem that needs to be solved urgently.
[0009] References:
[0010] Reference 1: Patent application 202310487511.X
[0011] Reference 2: Patent application 202211280713.9
[0012] Reference 3: Patent application 202310470563.6 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] In view of the technical problems existing in the prior art, the present invention provides a method for resource utilization of waste graphite. The method for resource utilization of waste graphite of the present invention is simple and easy to implement, the raw materials are easy to obtain, and the recycling of waste graphite and the coordinated treatment of new pollutants can be achieved.
[0015] The present invention also provides a catalyst, which can not only capture new pollutants such as antibiotics by using adsorption sites and catalytic centers, but also analyzes the unique gain effect of self-doped metals on the adsorption and degradation process of tetracycline hydrochloride.
[0016] In addition, the present invention also provides a use of a catalyst for in-situ enhancing the efficient capture and catalytic behavior of antibiotics, dyes or other types of pollutants.
[0017] Solutions for solving problems
[0018] [1] A method for recycling waste graphite, comprising the following steps:
[0019] The graphite-containing electrodes of the waste batteries are crushed to obtain crushed products;
[0020] Performing pyrolysis treatment on the crushed product to obtain a pyrolysis product;
[0021] The pyrolysis product is activated to obtain a catalyst.
[0022] [2] A method for recycling waste graphite, comprising the following steps:
[0023] The graphite-containing electrodes of the waste batteries are crushed to obtain crushed products;
[0024] Performing activation treatment on the crushed product to obtain an activated product;
[0025] The activated product is subjected to pyrolysis treatment to obtain a catalyst.
[0026] [3] The method according to [1] or [2] above, wherein the method further comprises screening the crushed product to obtain a screened product.
[0027] [4] The method according to [3] above, wherein the particle size of the sieved product is less than 0.1 mm, preferably less than 0.074 mm.
[0028] [5] A method according to any one of [1] to [4] above, wherein the pyrolysis treatment is carried out under vacuum conditions, air conditions or an inert atmosphere; preferably, the inert atmosphere includes one or both of a nitrogen atmosphere and an argon atmosphere.
[0029] [6] The method according to any one of [1] to [5] above, wherein the temperature of the pyrolysis treatment is 300 to 800°C and the time of the pyrolysis treatment is 30 to 180 minutes.
[0030] [7] The method according to any one of [1] to [6] above, wherein the activation treatment includes a mechanical ball milling step; preferably, the rotation speed of the mechanical ball milling is 300 to 700 r / min; and the mechanical ball milling time is 30 to 180 min.
[0031] [8] A catalyst, characterized in that it is prepared according to the method described in any one of [1] to [7] above.
[0032] [9] The catalyst according to [8] above, wherein the average pore size of the catalyst is 0.4-1 nm, and the specific surface area of the catalyst is 200-240 m 2 / g.
[0033]
[10] Use of the catalyst according to [8] above for catalytic oxidation of pollutants; preferably, the pollutants include antibiotics and / or dyes.
[0034] Effects of the Invention
[0035] The method for resource utilization of waste graphite of the present invention is simple and easy to implement, the raw materials are easy to obtain, and the recycling of waste graphite and the coordinated control of new pollutants can be achieved.
[0036] The catalyst of the present invention can not only capture new pollutants such as antibiotics by using adsorption sites and catalytic centers, but also analyzes the unique gain effect of self-doped metals on the adsorption and degradation process of tetracycline hydrochloride.
[0037] The catalyst of the present invention can be used to enhance the efficient capture and catalytic behavior of antibiotics, dyes or other types of pollutants in situ. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The present invention shows an overall process diagram of a method for recycling waste graphite, a catalyst and its use according to an embodiment of the present invention.
[0039] Figure 2 Raman spectra of different catalysts are shown.
[0040] Figure 3 BET diagrams of different catalysts are shown, wherein a is a comparison diagram of specific surface areas of different catalysts, and b is a diagram of isothermal adsorption curves and particle size distribution of different catalysts.
[0041] Figure 4 The graph shows the adsorption performance of tetracycline hydrochloride on different catalysts.
[0042] Figure 5 The graph shows the adsorption catalytic performance of catalysts in different experimental systems on tetracycline hydrochloride.
[0043] Figure 6 The graph shows the adsorption catalytic performance of the catalyst on tetracycline hydrochloride at different solution pH.
[0044] Figure 7 A catalyst cycle adsorption performance diagram is shown. DETAILED DESCRIPTION
[0045] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0046] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0047] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0048] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0049] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0050] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0051] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0052] <First aspect>
[0053] A first aspect of the present invention provides a method for resource utilization of waste graphite, which comprises the following steps:
[0054] The graphite-containing electrodes of the waste batteries are crushed to obtain crushed products;
[0055] Performing pyrolysis treatment on the crushed product to obtain a pyrolysis product;
[0056] The pyrolysis product is activated to obtain a catalyst.
[0057] The present invention prepares a catalyst by utilizing the self-doping metal property of waste graphite, thereby realizing resource utilization of waste graphite. The resource utilization method of waste graphite of the present invention is simple and easy to implement, the raw materials are easy to obtain, and the recycling of waste graphite and the coordinated treatment of new pollutants can be realized.
[0058] Used batteries
[0059] First, the electrodes of the waste battery of the present invention contain graphite. The present invention does not specifically limit the waste battery, as long as it contains graphite. Specifically, the waste battery can be a waste lithium battery. Specifically, the lithium battery can be a lithium cobalt oxide battery, a lithium iron phosphate battery, a ternary lithium battery or other types of lithium batteries.
[0060] For waste lithium batteries, waste graphite usually still has a good layered structure, and it is easy to form porous structures, defects and polar / oxygen-containing functional groups during repeated lithium insertion-extraction and electrolyte decomposition, and has good physical properties. In addition, the inventor accidentally discovered that the waste graphite itself is interspersed with residual metals such as Cu, Zr, Fe, Co, Ni, and Mn, which can be regarded as self-doped metals, which avoids the metal loading step in the conventional preparation process. Breaking through the cognition of these impurity metal residues, reversing their waste properties, and using them as adsorption sites and catalytic centers for capturing new pollutants such as antibiotics, this provides the possibility for the recycling of waste graphite and the coordinated governance of new pollutants.
[0061] The present invention reveals for the first time the occurrence characteristics of self-doped metals in graphite-containing electrodes of waste batteries, couples the physical properties of waste graphite itself, such as structural defects and active groups, to in situ enhance the efficient capture and catalytic behavior of antibiotics, and analyzes the unique gain effect of self-doped metals on the adsorption of antibiotics (for example, tetracycline hydrochloride TC) and the degradation process of antibiotics.
[0062] Crushing
[0063] In order to ensure the safety of the experimental process, the used batteries are safely discharged. Specifically, the used batteries can be discharged by physical short circuit, then immersed in NaCl solution for about 12-24 hours, and then dried in a fume hood. Until the battery voltage is less than 0.1V, the disassembly, crushing and other related experiments can be carried out.
[0064] In order to obtain the required catalyst, the graphite-containing electrode of the dismantled waste battery, such as the graphite anode, should be crushed to obtain a crushed product. Through the crushing process, large pieces of metal foil, such as copper foil, etc. can be removed to obtain the required waste graphite. The present invention does not specifically limit the crushing method, and it can be selected as needed, as long as the required crushed product can be obtained. Specifically, a shear crushing method can be used to obtain the required crushed product.
[0065] In some specific embodiments, the method further comprises screening the crushed product to obtain a sieved product, and then pyrolyzing the sieved product; preferably, the particle size of the sieved product is less than 0.1 mm, preferably less than 0.074 mm.
[0066] Pyrolysis treatment
[0067] In a first aspect of the present invention, the crushed product is subjected to pyrolysis treatment to obtain a pyrolysis product; some impurities can be removed by pyrolysis treatment, for example, surface impurities such as adhesives can be removed.
[0068] In some specific embodiments, in the present invention, the pyrolysis treatment can be carried out under vacuum conditions, in an air atmosphere or in an inert atmosphere, preferably in an inert atmosphere. When the crushed product is pyrolyzed in an inert atmosphere, the pyrolysis effect is better.
[0069] Specifically, in the present invention, the inert atmosphere means an atmosphere that does not chemically react with the crushed product. Preferably, the inert atmosphere includes one or both of a nitrogen atmosphere and an argon atmosphere. After the inert atmosphere is introduced, the pyrolysis product can effectively improve the removal rate of antibiotics. This may be because the inert gas promotes the pore development of the waste graphite, thereby increasing the specific surface area, and further promoting the adsorption of antibiotics by the waste graphite.
[0070] Further, in the present invention, the temperature of the pyrolysis treatment is 300-800°C, for example: 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, etc.; the time of the pyrolysis treatment is 30-180min, for example: 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, etc.
[0071] In addition, the present invention does not specifically limit the equipment for pyrolysis treatment, and it can be selected as needed. Specifically, in the present invention, the pyrolysis treatment can be carried out in a tube furnace or a muffle furnace, preferably in a tube furnace.
[0072] Activation treatment
[0073] In the first aspect of the present invention, the pyrolysis product is activated to obtain a catalyst. The catalyst prepared by pyrolysis and mechanical activation in the present invention avoids the addition of chemical reagents, has excellent catalytic ability and stability, and has a very high antibiotic removal rate in a wide pH range. This can not only promote the high-value utilization of waste graphite, conform to the principles of green chemistry and the concept of circular economy, but also achieve "waste treatment with waste" and contribute to the pollution control of new pollutants.
[0074] In some specific embodiments, the activation treatment includes the step of mechanically milling the pyrolysis product. Mechanical milling can refine the waste graphite particles and enhance the surface activity.
[0075] Preferably, the rotation speed of the mechanical ball mill is 300-700r / min, for example: 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, etc.; the mechanical ball milling time is 30-180min, for example: 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, etc.
[0076] In addition, the present invention does not specifically limit the activation equipment, and it can be selected as needed. Specifically, in the present invention, the activation can be performed mechanically using a ball mill.
[0077] The invention converts waste graphite into a catalyst with certain functionality and high specific surface area by pyrolysis treatment and then activation treatment. The catalyst has an average pore size of 0.4-1nm and an adsorption capacity of 200-450mg / g for pollutants.
[0078] The method of the present invention avoids the introduction of strong acid and strong oxidizing reagents in traditional methods such as the Hummers method, avoids the addition of chemical reagents such as metal-loaded reagents, and the used catalyst can be regenerated and recycled, thereby reducing costs to a certain extent. 催化剂 :V 污染物溶液 =(0.025g-0.1g):50mL) is relatively low, so it can be considered that the method has the potential to treat antibiotic wastewater. The method of the present invention provides a new way to realize the resource utilization of waste lithium battery waste graphite, and is also expected to become a candidate material for pollutant, such as antibiotic wastewater treatment.
[0079] The resource utilization method of waste graphite of the present invention is simple and easy to implement, the raw materials are easy to obtain, and the recycling of waste graphite and the coordinated treatment of new pollutants can be achieved.
[0080] <Second Aspect>
[0081] A second aspect of the present invention provides a method for resource utilization of waste graphite, which comprises the following steps:
[0082] The graphite-containing electrodes of the waste batteries are crushed to obtain crushed products;
[0083] Performing activation treatment on the crushed product to obtain an activated product;
[0084] The activated product is subjected to pyrolysis treatment to obtain a catalyst.
[0085] The used battery of the second aspect of the present invention is the same as the used battery of the first aspect.
[0086] Crushing
[0087] In order to ensure the safety of the experimental process, the used batteries are safely discharged. Specifically, the used batteries can be discharged by physical short circuit, then immersed in NaCl solution for 12-24 hours, and then dried in a fume hood. Until the battery voltage is less than 0.1V, the disassembly, crushing and other related experiments can be carried out.
[0088] In order to obtain the desired catalyst, the graphite-containing electrode of the waste battery, such as the graphite anode, should be crushed to obtain a crushed product. The present invention does not specifically limit the crushing method, and can be selected as needed, as long as the desired crushed product can be obtained. Specifically, a shear crushing method can be used to obtain the desired crushed product.
[0089] In some specific embodiments, the method further comprises screening the crushed product to obtain a sieved product, and then activating the sieved product; preferably, the particle size of the sieved product is less than 0.1 mm, preferably less than 0.074 mm.
[0090] Activation treatment
[0091] In a second aspect of the present invention, an activated product is obtained by subjecting the crushed product to an activation treatment.
[0092] In some specific embodiments, the activation treatment includes the step of mechanically ball milling the sieved product. Through mechanical ball milling, the waste graphite particles can be refined and the surface activity can be enhanced to a certain extent.
[0093] Preferably, the rotation speed of the mechanical ball mill is 300-700r / min, for example: 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, etc.; the mechanical ball milling time is 30-180min, for example: 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, etc.
[0094] In addition, the present invention does not specifically limit the activation equipment, and it can be selected as needed. Specifically, in the present invention, the activation can be performed mechanically using a ball mill.
[0095] Pyrolysis treatment
[0096] In the second aspect of the present invention, the catalyst is obtained by pyrolyzing the activated product; some impurities can be removed by pyrolysis, for example, surface impurities such as binders can be removed. However, when activation is performed first and then pyrolysis is performed, the removal rate of antibiotics will be reduced to a certain extent. This is because after pyrolysis to remove the binder, mechanical activation will make the particles have a higher specific surface area, which far exceeds activation first and then pyrolysis.
[0097] In some specific embodiments, in the present invention, the pyrolysis treatment can be carried out under vacuum conditions, in air atmosphere or in an inert atmosphere, preferably in an inert atmosphere. When the activated product is pyrolyzed in an inert atmosphere, the pyrolysis effect is better.
[0098] Specifically, in the present invention, the inert atmosphere means an atmosphere that does not chemically react with the activated product. Preferably, the inert atmosphere includes one or both of a nitrogen atmosphere and an argon atmosphere.
[0099] Further, in the present invention, the temperature of the pyrolysis treatment is 300-800°C, for example: 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, etc.; the time of the pyrolysis treatment is 30-180min, for example: 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, etc.
[0100] In addition, the present invention does not specifically limit the pyrolysis equipment, and it can be selected as needed. Specifically, in the present invention, the pyrolysis can be carried out in a tube furnace or a muffle furnace, preferably in a tube furnace.
[0101] The catalyst prepared by the present invention by first performing mechanical activation treatment and then performing pyrolysis treatment avoids the addition of chemical reagents, but the antibiotic removal rate is lower than that of first performing pyrolysis treatment and then performing mechanical activation treatment.
[0102] In addition, the inventors of the present invention have found that when activation is performed first and then pyrolysis is performed, the removal rate of antibiotics will be reduced to a certain extent. This is because the particles will have a higher specific surface area after pyrolysis to remove the binder, and then mechanical activation, which is far greater than activation first and then pyrolysis.
[0103] <Third Aspect>
[0104] The third aspect of the present invention provides a catalyst, which is prepared by the method described in the first aspect or the second aspect of the present invention. The present invention realizes the recycling and reuse of waste battery anode graphite by preparing antibiotic catalyst from waste lithium battery anode graphite.
[0105] The catalyst of the present invention has a simple preparation process, avoids the addition of foreign chemical reagents, and successfully converts waste battery graphite into a catalyst by pyrolysis and mechanical activation. The method of the present invention realizes the low-cost green resource utilization of waste graphite, and at the same time realizes "waste treatment with waste", making contributions to the pollution control of new pollutants.
[0106] Preferably, the average pore size of the catalyst is 0.4-1 nm, for example, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, etc.; the specific surface area of the catalyst is 200-240 m 2 / g, for example: 205m 2 / g, 210m 2 / g, 215m 2 / g, 220m 2 / g, 225m 2 / g, 230m 2 / g, 235m 2 / g, etc.
[0107] The catalyst of the present invention can induce an oxidant to generate free radicals, and degrade antibiotics by adsorption and catalysis. Specifically, the oxidant can be an inorganic oxidant, specifically a peroxide oxidant (for example: hydrogen peroxide, etc.), a persulfate oxidant (for example: sodium persulfate, potassium persulfate, magnesium persulfate), etc.
[0108] The catalyst of the present invention can not only capture and degrade new pollutants such as antibiotics through adsorption sites and catalytic centers, but also analyzes the unique gain effect of self-doped metals in graphite on the adsorption and degradation process of pollutants such as tetracycline hydrochloride.
[0109] <Fourth Aspect>
[0110] The fourth aspect of the present invention provides a use of the catalyst according to the third aspect of the present invention for catalytic oxidation of pollutants; preferably, the pollutants include antibiotics and / or dyes. For antibiotics, it can be tetracycline hydrochloride and the like.
[0111] In some specific embodiments, in the present invention, generally catalytic oxidation is performed on the pollutant solution. That is, in the presence of the catalyst of the present invention, the pollutant solution is subjected to catalytic oxidation treatment using an oxidant. Specifically, the oxidant is generally an inorganic oxidant, such as a peroxide oxidant, a persulfate oxidant, etc. For the peroxidant oxidant, generally hydrogen peroxide, etc., and for the persulfate oxidant, sodium persulfate, potassium persulfate, magnesium persulfate, etc.
[0112] Furthermore, the present invention does not specifically limit parameters such as the time of the catalytic oxidation reaction between the oxidant and the pollutant, the concentration of the pollutant, the pH value of the pollutant, the dosage of the catalyst, the dosage of the oxidant, and the solid-liquid ratio of the catalyst, and they can be selected as needed.
[0113] Specifically, in the pollutant solution, the concentration of the pollutant can be 100-250 mg / L; the pH of the pollutant solution is adjusted to 2-11; the catalytic oxidation reaction time is 2-60 min; the amount of catalyst added is 0.025 g-0.1 g, and the volume of the pollutant solution is 50 mL, that is, the solid-liquid ratio of the catalyst to the pollutant solution is m 催化剂 :V 污染物溶液 (0.025g~0.1g):50mL; the dosage of the oxidant (taking hydrogen peroxide as an example) is 0~3vol.%.
[0114] Preferably, the pH of the pollutant solution is adjusted to 3-7, the catalytic oxidation reaction time is 2-30 min, the dosage of the catalyst is 0.025 g-0.05 g, and the dosage of the oxidant (for example, hydrogen peroxide) is 0.1-1 vol.%.
[0115] In addition, the present invention does not specifically limit the equipment for the catalytic oxidation reaction of the pollutants by the catalyst, and can be selected as needed. Specifically, in the present invention, the reaction can occur in a water bath shaker or a water bath pot.
[0116] The catalyst of the present invention does not need to be loaded with metal reagents and is simple to prepare. It can efficiently treat pollutants such as antibiotics through simple pyrolysis and activation. Specifically, the adsorption capacity of the antibiotic tetracycline hydrochloride is 200-450 mg / g.
[0117] Example
[0118] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0119] In the embodiment, in order to ensure the safety of the experimental process, the waste ternary lithium battery anode sheet used is safely discharged. Specifically, the waste battery can be discharged by physical short circuit, then immersed in 5wt% NaCl solution for about 12-24 hours, and then dried in a fume hood. Until the battery voltage is less than 0.1V.
[0120] Example 1
[0121] The discharged waste ternary lithium battery anode sheet is sheared and crushed to obtain a crushed product. The crushed product is sieved with a 0.074 mm sieve to remove large pieces of Cu to obtain relatively pure sieved graphite.
[0122] The screened graphite is fed into a tubular furnace for medium-low temperature pyrolysis to obtain pyrolytic graphite, wherein the pyrolysis atmosphere is set to N2, the pyrolysis temperature is set to 400°C, and the pyrolysis time is set to 30 minutes for each pyrolysis.
[0123] The pyrolytic graphite was placed in a ball mill for mechanical activation to obtain a catalyst, which was recorded as PMG. The mechanical activation time was set to 120 min and the speed of the ball mill was 600 r / min.
[0124] Example 2
[0125] The discharged waste ternary lithium battery anode sheet is sheared and crushed to obtain a crushed product. The crushed product is sieved with a 0.074 mm sieve to remove large pieces of Cu to obtain relatively pure sieved graphite.
[0126] The screened graphite is placed in a ball mill for mechanical activation to obtain activated graphite. The mechanical activation time is set to 120 minutes and the speed of the ball mill is 600 r / min.
[0127] The activated graphite is fed into a tube furnace for medium-low temperature pyrolysis to obtain a catalyst, which is recorded as MPG. The pyrolysis atmosphere of each pyrolysis is set to N2, the pyrolysis temperature is set to 400°C, and the pyrolysis time is set to 30 minutes.
[0128] Example 3
[0129] The discharged waste ternary lithium battery anode sheet is sheared and crushed to obtain a crushed product. The crushed product is sieved with a 0.074 mm sieve to remove large pieces of Cu to obtain relatively pure sieved graphite.
[0130] The screened graphite is fed into a tubular furnace for medium-low temperature pyrolysis to obtain pyrolytic graphite. The pyrolysis atmosphere of each pyrolysis is set to N2. The pyrolysis temperature is set to 400°C and the pyrolysis time is set to 30 minutes.
[0131] The pyrolytic graphite was placed in a ball mill for mechanical activation to obtain a catalyst, which was recorded as PMG-2. The mechanical activation time was set to 60 minutes and the speed of the ball mill was 600 r / min.
[0132] Comparative Example 1
[0133] 200 mesh natural graphite (purchased from Nanjing Ge Ruifa Carbon Materials Co., Ltd.), recorded as NG.
[0134] Comparative Example 2
[0135] The discharged waste lithium battery anode sheet is sheared and crushed to obtain a crushed product. The crushed product is sieved with a 0.074 mm sieve to remove large pieces of Cu to obtain relatively pure sieved graphite, which is recorded as: SG.
[0136] Comparative Example 3
[0137] The discharged waste lithium battery anode sheet is sheared and crushed to obtain a crushed product. The crushed product is sieved with a 0.074 mm sieve to remove large pieces of Cu to obtain relatively pure sieved graphite.
[0138] The screened graphite is fed into a tubular furnace for medium-low temperature pyrolysis to obtain pyrolytic graphite, which is recorded as PG. The pyrolysis atmosphere of each pyrolysis is set to N2. The pyrolysis temperature is set to 400°C and the pyrolysis time is set to 30 minutes.
[0139] Comparative Example 4
[0140] The discharged waste lithium battery anode sheet is sheared and crushed to obtain a crushed product. The crushed product is sieved with a 0.074 mm sieve to remove large pieces of Cu to obtain relatively pure sieved graphite.
[0141] The screened graphite was placed in a ball mill for mechanical activation to obtain activated graphite, which was recorded as MG. The mechanical activation time was set to 120 min and the speed of the ball mill was 600 r / min.
[0142] Performance Testing
[0143] 1. Raman characterization
[0144] The defects of the catalysts prepared in Example 1 and Comparative Examples 1-4 were characterized using a laser Raman spectrometer, as shown in the attached figure. Figure 2 As shown. Among them, the D peaks of the natural graphite NG and SG sieved graphite of Comparative Examples 1 and 2 are very weak, indicating that the defect density of the catalyst is low. The S peaks of the pyrolytic graphite PG of Comparative Example 3 and the catalyst PMG of Example 1 are D / S G The ratio of S to SG is significantly increased, increasing to 0.68 and 1.19 respectively. D / S G The ratio indicates that the defects and disordered structures of the catalysts increase, which can provide more reaction sites. In addition, compared with SG, the G peaks of PG and PMG increase from 1568 cm-1 of SG to 2567 cm-2 of SG, respectively. -1 Offset to 1578cm -1 and 1570cm -1 The shift of the G-band Raman scattering peak position is due to the change in the electronic structure caused by the increase in the disorder of the catalyst structure.
[0145] 2. BET Characterization
[0146] The specific surface area and pore size distribution of the catalysts prepared in Example 1 and Comparative Examples 1-4 were characterized using a specific surface area porosity analyzer, as shown in the attached Figure 3 Compared with natural graphite NG, sieved graphite SG, and pyrolytic graphite PG, the catalyst PMG has the largest specific surface area and pore volume, which are 237.2m 2 / g and 0.3954cm 3 / g, which further illustrates that pyrolysis and mechanical activation treatments are beneficial to pore development, and mechanical force impacts, shears and grinds the graphite material into smaller particles.
[0147] BET characterization shows that the isotherms of NG, SG, and PG belong to type III in the IUPAC classification. The adsorption curve shows that at low and medium relative pressures, the adsorption amount is small and the monolayer adsorption is saturated. With the increase of relative pressure, the adsorption shows a self-acceleration phenomenon, and the number of adsorption layers is not limited. The isotherm of PMG belongs to type IV in the IUPAC classification, with an H4 hysteresis loop. The low-pressure end catalyst has a strong interaction with nitrogen, indicating that there are more micropores. Due to the strong adsorption potential in the micropores, the adsorption curve is type I at the beginning.
[0148] The pore size distribution diagram further proves that pyrolysis and mechanochemical treatment transform SG from original macropores to more micropores and mesopores. In summary, PMG after pyrolysis and mechanical activation has a larger specific surface area and more micropores / mesoporous structures, which will improve the adsorption performance of the catalyst.
[0149] 3. Adsorption performance test of tetracycline hydrochloride (TC)
[0150] 50 mL of 150 mg / L tetracycline hydrochloride solution and 0.1 g of the catalyst prepared in Example 1-2 and the carbon material prepared in Comparative Example 1-4 were added to a conical flask, the shaking speed was set to 200 r / min, the temperature was 30°C, and the reaction time was 60 min. The solution was then filtered and the concentration of TC in the solution was measured using high performance liquid chromatography (HPLC), and the TC removal rate and catalyst adsorption amount were calculated. The adsorption performance of the catalyst prepared in Example 1-2 and the graphite material prepared in Comparative Example 1-4 on tetracycline hydrochloride is shown in the attached figure. Figure 4 shown.
[0151] It can be seen from Comparative Examples 3 and 4 that both pyrolysis and mechanical activation can improve the removal rate of tetracycline hydrochloride by waste graphite, and the removal rates of tetracycline hydrochloride by the two are comparable. 2 / g) than pyrolytic graphite PG (7.5m 2 This is mainly due to the fact that the binder on the SG surface hinders the binding of tetracycline hydrochloride to the SG surface sites.
[0152] In addition, the order of pyrolysis and mechanical activation coupling will also have a certain impact. The removal rate of tetracycline hydrochloride by catalyst PMG was significantly increased to 93.9%, which is higher than the 72% of catalyst MPG. This may be because PMG, which is pyrolyzed first and then mechanically activated, is looser and is more easily mechanically compressed, sheared, and impacted into smaller particles after losing the binder impurities. These small particles have a higher specific surface area, which is much higher than the specific surface area of MPG.
[0153] 4. Catalytic effect verification experiment
[0154] Experimental system for verifying the catalytic effect of self-doped metal in waste graphite: In a 250mg / L tetracycline hydrochloride solution, ① only the catalyst PMG prepared in Example 1 was added, ② only 0.5vol% hydrogen peroxide was added, ③ the catalyst PMG prepared in Example 1 and 0.5vol% hydrogen peroxide were added, ④ the catalyst (APMG) of Example 1 after self-doped metal ions were removed by leaching with 2mol / L sulfuric acid was added, and ⑤ the catalyst (APMG) of Example 1 after self-doped metal ions were removed by leaching with 2mol / L sulfuric acid and 0.5%vol hydrogen peroxide were added. The concentration of tetracycline hydrochloride was detected by HPLC, and the mineralization rate was detected and calculated by a total organic carbon analyzer (TOC). The results are as follows: Figure 5 shown.
[0155] Depend on Figure 5 It can be seen that in the experiment using only PMG, due to the adsorption of the catalyst, the removal efficiency of tetracycline hydrochloride reached 41.8%, and the total organic carbon (TOC) removal rate reached 36.8%. In the system using only hydrogen peroxide without the presence of a catalyst, the removal rate of hydrogen peroxide for tetracycline hydrochloride reached 36.2%, but the mineralization rate was almost 0.
[0156] In the experiment using catalyst PMG and hydrogen peroxide, the removal rates of tetracycline hydrochloride and total organic carbon in the PMG / hydrogen peroxide system were much higher, reaching 100% and 53.6%, respectively. The total organic carbon removal rate was much lower than that of tetracycline hydrochloride, which was attributed to the generation of intermediates after the degradation of tetracycline hydrochloride. The addition of PMG significantly promoted the degradation and mineralization of TC by hydrogen peroxide. This may be because the doped metals in graphite (such as Fe, Co, Ni, Mn, Cu, etc.) can act as catalytic centers, catalyzing hydrogen peroxide to produce more available strong oxidizing reaction species, thereby promoting the oxidative degradation reaction of TC molecules.
[0157] In addition, in the experiment of leaching the catalyst PMG and hydrogen peroxide after doping with metal ions using sulfuric acid, the removal rate of tetracycline hydrochloride decreased from 100% before acid leaching to 32%, which further verified the important role of doped metals in graphite-containing electrodes in catalysis.
[0158] 5. Antibiotic wastewater pH adjustment experiment
[0159] 50mL of 250mg / L tetracycline hydrochloride solution was added to a conical flask, and the solution pH was adjusted to 2, 3, 5, 7, 9, and 11 using 1mol / L H2SO4 or 1mol / LNaOH. The catalyst PMG prepared in Example 1 and 0.5vol% hydrogen peroxide were then added to the pH-adjusted and pH-unadjusted tetracycline hydrochloride solutions (pH about 3-5), respectively. The shaking speed was set to 200r / min, the temperature was 30°C, and the reaction time was 2h. The relevant results are shown in the attached figure. Figure 6shown.
[0160] The catalyst has excellent adsorption catalytic effect on tetracycline hydrochloride at different pH values. PMG not only has adsorption performance, but also has excellent catalytic activity and tetracycline hydrochloride mineralization rate. pH value is one of the important influencing factors of Fenton-like oxidation. In a wide pH range, the PMG / H2O2 system shows a high TC removal rate.
[0161] 6. Catalyst cycle adsorption-regeneration experiment
[0162] The pH of the tetracycline hydrochloride solution was adjusted to 3 and 5 respectively, and 250 mg / L of tetracycline hydrochloride solution, the catalyst PMG prepared in Example 1 and 0.5 vol% hydrogen peroxide were added to a conical flask, the shaking speed was set to 200 r / min, the temperature was 30°C, and the reaction time was 30 min; after reacting for 30 min, the adsorbed PMG was filtered, pyrolyzed at 350°C for 1 h to regenerate PMG, and then put into the next round of experiments, which were repeated 4 to 5 times. The relevant results are shown in the attached Figure 7 shown.
[0163] The catalyst PMG of Example 1 has the potential for reuse. During the four cycles, whether the pH value is 3 or pH value is 5, the catalyst maintains extremely high adsorption and catalytic degradation capabilities, and all cycles show a tetracycline hydrochloride removal efficiency of more than 95%. The catalyst can be regenerated by heating at medium and low temperatures to decompose tetracycline hydrochloride. This shows that the catalyst has good reusability and high adsorption and catalytic capabilities, and has commercial application potential.
[0164] 7. Calculation of TC adsorption capacity
[0165] The catalyst of Example 1 and simulated tetracycline hydrochloride wastewater (100-250 mg / L) were mixed at a certain solid-liquid ratio (m 催化剂 :V 抗生素废水 =0.025g~0.1g:50mL) was added to a conical flask, the shaking speed was set to 200r / min, and the temperature was 30°C. After the adsorption was completed, the liquid was filtered with a 0.22μm filter head, and the filtrate was collected and HPLC and total organic carbon tests were used to determine the concentrations of tetracycline hydrochloride and total organic carbon to evaluate the catalytic and mineralization effects of porous graphite on antibiotics.
[0166] Adsorption capacity Q t Press Q t =(ρ0-ρ1)V / m calculation, where Q t is the adsorption capacity at time t, mg / g; ρ0 is the mass concentration of lithium ions in the initial solution, mg / L; ρ1 is the mass concentration of lithium ions after adsorption, mg / L; m is the mass of the adsorbent, g; V is the volume of the adsorption solution, L. The results are shown in Figure 4, 6 , as shown in Figure 7.
[0167] The results show that the catalyst PMG prepared in Example 1 has a high adsorption performance for tetracycline hydrochloride, and the adsorption capacity is as high as 209.0 mg / g.
[0168] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0169] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for recycling waste graphite, characterized in that: The following steps are involved: The graphite-containing electrodes of the waste batteries are crushed to obtain crushed products; Performing pyrolysis treatment on the crushed product to obtain a pyrolysis product; The pyrolysis product is activated to obtain a catalyst.
2. A method for recycling waste graphite, characterized in that: The following steps are involved: The graphite-containing electrodes of the waste batteries are crushed to obtain crushed products; Performing activation treatment on the crushed product to obtain an activated product; The activated product is subjected to pyrolysis treatment to obtain a catalyst.
3. The method according to claim 1 or 2, characterized in that: The method further comprises screening the crushed product to obtain a screened product.
4. The method according to claim 3, characterized in that The particle size of the sieved product is less than 0.1 mm, preferably less than 0.074 mm.
5. The method according to any one of claims 1 to 4, characterized in that: The pyrolysis treatment is carried out under vacuum conditions, air conditions or an inert atmosphere; preferably, the inert atmosphere includes one or both of a nitrogen atmosphere and an argon atmosphere.
6. The method according to any one of claims 1 to 5, characterized in that: The temperature of the pyrolysis treatment is 300 to 800° C.; the time of the pyrolysis treatment is 30 to 180 minutes.
7. The method according to any one of claims 1 to 6, characterized in that: The activation treatment includes a step of mechanical ball milling; preferably, the rotation speed of the mechanical ball milling is 300 to 700 r / min; and the mechanical ball milling time is 30 to 180 min.
8. A catalyst, characterized in that The method comprises preparing the product according to any one of claims 1 to 7.
9. The catalyst according to claim 8, characterized in that The average pore size of the catalyst is 0.4-1 nm, and the specific surface area of the catalyst is 200-240 m 2 / g.
10. Use of the catalyst according to claim 8 for catalytic oxidation of pollutants; preferably, the pollutants include antibiotics and / or dyes.
Citation Information
Patent Citations
Method for preparing supercapacitor electrode material by using waste lithium battery graphite
CN115662804A
Method for preparing graphene oxide by improved Hummers method
CN116239109A
Waste lithium ion battery regenerated graphite negative electrode based on organic acid pyrolysis gas phase reduction and regeneration method thereof
CN116779850A
Method for removing organic pollutants in water
CN113087118A
Recycling method of negative electrode graphite of waste lithium battery
CN113437381A
